Anther transcriptomes in cold-tolerant rice cultivars tend to show insensitive responses - Koichi Yamamori; Seiya Ishiguro; Kei Ogasawara; Kayyis Muayadah Lubba; Kaien Fujino; Kazumitsu Onishi; Yutaka Sato; Yuji Kishima (Plant Stress)
Many studies of stress tolerance in plants have characterized genes that show differences among a small number of lines with clearly distinct tolerance or sensitivity to the given stress. From the few cloned genes, it is difficult to genetically interpret intermediate tolerance or susceptibility levels and explain the complexity of stress responses and tolerance. In this study, we explored the changes in the transcriptome of anthers from 13 rice lines with different cold tolerance grown under control conditions or exposed to 4 days of cold stress to look for correlations between cold tolerance at the booting stage and expression levels. When examining the overall expression patterns in anthers at low temperature, the cold-tolerant lines tended to have relatively few highly expressed genes, and the expression levels of ribosome-related genes tended to be lower in cold-tolerant lines than in cold-sensitive lines. Importantly, we observed these different expression patterns between the cold-tolerant and -sensitive lines regardless of whether cold stress had been applied. Minimal changes in genes and repetitive sequences under cold stress also tended to be characteristic of the cold-tolerant lines. We also identified unknown genes whose expression was cold responsive and common to all the lines studied. The rice lines whose transcriptome remains constant or insensitive in response to cold stress are more tolerant to low-temperature exposure during the booting stage than rice lines with more widespread expression changes.